Establishment and evaluation of a patient-derived organoids-based xenograft model of primary aldosteronism using [18F]AlF-NOTA-pentixather PET/CT: bridging preclinical and clinical imaging - Xuezhou Zhang; Tiantian Mou; Yuxuan Wang; Qi Miao; Wei Wang; Zhipeng Sun; Yuxuan Bo; Jiayuan Cui; Jiahui Zhao; Mingchuan Li; Baoan Hong; Hongzhi Mi; et al. (Journal of Translational Medicine)
Abstract Background Primary aldosteronism (PA) is a leading cause of secondary hypertension, but the lack of representative preclinical models hampers translational research and imaging evaluation. We aimed to establish a patient-derived organoids-based xenograft (PDOX) model of PA and to assess its imaging characteristics using [18F]AlF-NOTA-pentixather PET/CT, with validation in clinical patients. Methods Adrenal tissues from patients with PA were used to generate adrenal organoids in vitro. After serial passaging, these organoids were implanted subcutaneously into immunodeficient mice to establish PA PDOX models. The xenografted mice were subjected to [18F]AlF-NOTA-pentixather PET/CT to evaluate tracer uptake and lesion detectability. In parallel, clinical PA patients underwent [18F]AlF-NOTA-pentixather PET/CT to assess the imaging performance in a clinical setting. Results The PDOX models successfully engrafted and proliferated in vivo, maintaining key pathological features of PA. [18F]AlF-NOTA-pentixather PET/CT imaging in the PDOX models demonstrated high and specific tracer uptake in xenografted lesions, with strong concordance to histopathological findings. In clinical PA patients, [18F]AlF-NOTA-pentixather PET/CT also showed excellent performance in localizing PA lesions and provided valuable diagnostic information. Conclusion We established a novel PDOX model of PA and demonstrated the effectiveness of [18F]AlF-NOTA-pentixather PET/CT in both preclinical and clinical applications. This approach provides a robust translational platform for mechanistic studies and for advancing precision imaging and therapy in PA.